Outcome of hemodialysis in elderly diabetic patients: a single-center experience - Hatem Darwish; Ahmed Fathi (SpringerOpen, 2015)
Background The optimal renal replacement therapy for elderly patients is unclear, and literature is evolving in this regard. For elderly individuals who progress to CKD5, hemodialysis is often a valuable treatment option. Although hemodialysis is a life-sustaining therapy and extends life, it may also create, increase, or prolong suffering in selected subgroups of geriatric patients. In our current study we focused on elderly diabetic patients above 65 years, as they constitute the more vulnerable subgroup, having multiple comorbid conditions. The primary objective was to study the patient's survival and the association with different comorbidities. Patients and methods We conducted a retrospective analysis of 48 type 2 diabetic patients aged above 65 years. We reviewed their survival data and comorbid conditions - namely, vascular, cognitive, and autonomy. Results and Conclusion The mortality rate was 7.5% per year with significant association with prior cerebrovascular accident, cognitive impairment, and lost autonomy.